2017
DOI: 10.3233/wor-172580
|View full text |Cite
|
Sign up to set email alerts
|

The importance of assistive technology in the productivity pursuits of young adults with disabilities

Abstract: Young adults with disabilities draw on their experiences of AT use but may need to develop advocacy skills to ensure their needs are met in productivity-related environments. Employers and supervisors should recognize AT as essential to young adult's engagement with productivity-related activities and have an important role in developing inclusive work environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
(29 reference statements)
0
11
0
8
Order By: Relevance
“…Environmental supports were also identified; an accessible work environment in which accommodations were made to meet the employee's needs, optimized performance and facilitated engagement in the workplace [30,38]. Many employees reported working from home [25,33,38] and using assistive technology such as Dictaphones, dual monitors, assistive devices for communication and computerized phones and alarms, positively impacted work satisfaction and work maintenance [33,[39][40][41].…”
Section: Products and Technology/natural Environment And Human-made Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Environmental supports were also identified; an accessible work environment in which accommodations were made to meet the employee's needs, optimized performance and facilitated engagement in the workplace [30,38]. Many employees reported working from home [25,33,38] and using assistive technology such as Dictaphones, dual monitors, assistive devices for communication and computerized phones and alarms, positively impacted work satisfaction and work maintenance [33,[39][40][41].…”
Section: Products and Technology/natural Environment And Human-made Cmentioning
confidence: 99%
“…For example, stereotypes associated with this population such as their inability to work, their need for costly accommodations or their unwillingness to be active members, hindered persons with a disability to exhibit and exercise their skills in the workplace. This was evident in various types of brain-based disabilities, including physical, intellectual and sensory related impairments [39,52,53]. In one study, it was found that this negative perception and discrimination led to higher rates of unlawful discharge of young adults with epilepsy as compared to their colleagues [51].…”
Section: Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the emerging young elderly group has shown higher adoption rates (Mostaghel 2016). Likewise, younger people with disabilities are more willing to experiment with AT: They are often very goal and task orientated, seeking to enhance their independence and performance (Ripat and Woodgate 2017). Crucially, Roentgen et al (2012) have highlighted that individual needs and preferences are important determining factors in the acceptance and adoption of ETAs over time.…”
Section: Research Contextmentioning
confidence: 99%
“…These people should be empowered to be involved in the process where communication involves and embraces them, even those who do not have functional speech or writing (Dudas, 2013). Companies that provide individual support to their employees with disabilities, clearly and objectively transmitting to them the values and vision of the organization and helping them integrate into the work environment, showed a greater permanence of these individuals in employment (Ripat & Woodgate, 2017;Scott et al, 2015).…”
Section: Interpersonal Communication (Ic)mentioning
confidence: 99%